FUNGSI DAN KEDUDUKAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 1999 DAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Sihotang, Angga Alfonsus; Jayakusuma, Zulfikar; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The DPRD remains in place as an organizing element of regional government, andcontinues to have the authority to jointly discuss draft regional regulations with regionalheads, discuss and determine the APBD with regional heads, and has a role as supervisor ofthe implementation of mutually approved Regional Regulations and mutually approvedAPBDs. This means that the DPRD is a working partner of the regional head in administeringregional government as intended by Law Number 23 of 2014 concerning regional government.If the DPRD is said to be a legislative institution, it is not correct, because the DPRD is not anabsolute institution that has the power of a legislative institution like the DPR RI.The aims of writing this thesis are: first, to find out the function and position of the DPRDbased on Law Number 22 of 1999 and Law Number 23 of 2014 concerning RegionalGovernment. Second, to understand the ideal concept of the function and position of the DPRDin the Regional Government system. The research method in this thesis uses a type of normativejuridical research, namely research that focuses on examining the application of rules ornorms in positive law. The nature of this thesis research is researchdescriptivewhichsystematically describes the facts and characteristics of the object being studied accurately.The data source used is the data sourcefirst, seconds andtertiary, The data collection methodused in this research is firstly literature study, which is a technique for obtaining secondarydata through documents related to the problem, objectives and benefits of the research, thenafter the data is collected it is then analyzed to draw conclusions.Based on the research results, Law No. 22 of 1999 stipulates that the DPRD is theregional legislative body and the regional government is the regional executive body. So in thiscase the position of the DPRD is separate from the regional government organs, whereas inLaw No. 23 of 2014 the district/city regional government consists of the district/city regionalgovernment so that in this case the position of the DPRD is a working partner of the regionalhead in administering government, secondly, the ideal pattern of relationship between thelegislature and the executive is a balance between the two institutions, but this will reallydepend on the political system being built. In connection with the position of the DPRD as aworking partner on an equal footing with the Regional Head, legal products in the form ofRegional Government Law No. 23 of 2014 must be emphasized regarding the position of theDPRD in the regional government system. Even though it is stated that they are equal in thelaw, the actual situation places the DPRD under the Regional Head. This causes the DPRD'sperformance to be ineffective based on what is mandated by lawKeywords: Law, Government, DPRD.